PENGARUH RISIKO DALAM PRAKTIK PENERAPAN MANAJEMEN RISIKO PADA PERBANKAN SYARIAH BERDASARKAN PRINSIP ISLAMIC FINANCIAL SERVICES BOARD (IFSB) Studi Kasus Pada Salah Satu Bank Syariah Peraih Global Islamic Finance Award 2021 Di Indonesia - Theodorus Pradipta Paramarta; Wahyu Meiranto (Diponegoro Journal of Accounting, 2022)
The purpose of this research is to look at risk management practices in Islamic banking in Indonesia by using all the risks that exist in banking institutions. This research aims to find out about the practice of implementing risk management in sharia banking in Indonesia by using all the risks that exist in banking institutions.This study uses quantitative methods. The sample used in this study is one of the winner of Global Islamic Finance Award 2021 in Indonesia. The researcher cannot reveal the name of the Islamic  bank because they are undergoing the adjustment process due to the renewal. Retrieval of data for research using the questionnaire method.Data analysis uses multiple linear regression. This analysis proves that the credit risk, investment risk, liquidity risk, and operational risk greatly affects the practice of implementing risk management in Islamic banks. However, market risk and commercial displaced risk does not influence the application of risk management.